A comparative picture of the ease of use and acceptance of onscreen marking by markers across subject areas. (18th May 2015) - Coniam, David; Yan, Zi
Abstract: Onscreen marking (OSM) has been used for the majority of Hong Kong public examinations since 2012. The current study compares marker reactions to OSM, ie, perceived ease of use and acceptance of OSM, against the backdrop of virtually all subject areas being marked on screen. The data were collected from three major sources: (1) survey data obtained from 1743 markers across 14 major subject areas, (2) markers' qualitative comments about the OSM system and (3) post‐hoc interviews with a key informant from the Hong Kong Examinations and Assessment Authority (HKEAA). Results showed that, in general, markers revealed a high level of perceived ease of use and positive acceptance of OSM. The effect of subject area for both scales was statistically significant. On the E ase of U se in the OSM Environment scale, markers of information and communication technology (ICT) and mathematics were the most positive, with markers of history and geography the least positive. On the A cceptance of OSM scale, markers of mathematics and ICT were the most accepting, with markers of biology and geography the least. The analysis of survey data was triangulated by markers' qualitative comments together with the HKEAA staff interview. Possible explanations for the results are proposed and implications for the further development of OSM are briefly discussed.